2009
DOI: 10.1523/jneurosci.2406-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Period for Activity-Dependent Synaptic Development during Olfactory Bulb Adult Neurogenesis

Abstract: New neurons integrate in large numbers into the mature olfactory bulb circuit throughout life. The factors controlling the synaptic development of adult-born neurons and their connectivity remain essentially unknown. We examined the role of activity-dependent mechanisms in the synaptic development of adult-born neurons by genetic labeling of synapses while manipulating sensory input or cell-intrinsic excitability. Sensory deprivation induced marked changes in the density of input and output synapses during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
140
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(154 citation statements)
references
References 35 publications
12
140
2
Order By: Relevance
“…Spine density in the proximal compartment of adult-born GCs peaks at 15-30 d before further pruning at 90 dpi (29). Moreover, impairing NMDA receptors decreases the proximal spine density but sensory deprivation distinctly alters proximal and basal domains (22,31). Collectively, these data indicate that sensory experience strongly influences the direction and location of structural synaptic plasticity.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Spine density in the proximal compartment of adult-born GCs peaks at 15-30 d before further pruning at 90 dpi (29). Moreover, impairing NMDA receptors decreases the proximal spine density but sensory deprivation distinctly alters proximal and basal domains (22,31). Collectively, these data indicate that sensory experience strongly influences the direction and location of structural synaptic plasticity.…”
Section: Discussionmentioning
confidence: 81%
“…Developmental analysis of apical spine density in adult-born GCs has shown a progressive increase at 15-30 dpi followed by a slight decrease and stabilization at 50-90 d (28)(29)(30). Olfactory deprivation between 15 and 30 dpi strongly reduces apical spine density (22), whereas passive odorant exposure has no significant effect on spine density (29) but decreases spine turnover (8). We also confirmed that neither odor exposure nor odor learning affects apical spine density and maturation, suggesting that apical spine turnover, rather than the total number of spines, is impacted by sensory experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue processing and analysis of PSD-95GFP ϩ clusters was performed as previously described (Kelsch et al, 2009). Confocal image stacks were acquired using a Zeiss LSM700 (63ϫ oil-immersion objective) (512 ϫ 512 pixel with pixel size of 0.196 ϫ 0.196 m), and with z-step 0.25 m (80 -150 sections).…”
Section: Methodsmentioning
confidence: 99%
“…Adult-born GCs are generated in the subventricular zone (SVZ) and migrate to the OB where they form synaptic connections during a narrow time window (Carleton et al, 2003;Whitman and Greer, 2007;Kelsch et al, 2008). Only during this period of synaptic development, sensory deprivation changes the synaptic organization of glutamatergic synapses and increases cell death of adult-born GCs (Yamaguchi and Mori, 2005;Kelsch et al, 2009).…”
Section: Introductionmentioning
confidence: 99%